Negotiation, adoption and domestic implementation of the annex on liability to the Protocol on Environmental Protection to the Antarctic Treaty - Ferrada, Luis V.; Caldera, Diego A. (Antarctic Science, 2024)
Abstract Rules on liability are essential to ensuring the enforcement of an international agreement. The Antarctic Treaty Consultative Meeting's adoption of Measure 1 (2005), which contains Annex VI to the Protocol on Environmental Protection, is the first step towards complying with Article 16 of the Environmental Protocol on Liability. However, the approval process has been slow, and Measure 1 (2005) is still not in force. Here, we show a need for more momentum in its approval and that its domestic implementation varies significantly. Only 19 states have approved Measure 1 (2005) out of the 28 Consultative Parties required to enter into force. Ten have incorporated national provisions anticipating its entry into force. Our study suggests that the perceived inadequacy of Annex VI, the cost of response actions to environmental emergencies and the misplaced importance of Antarctic matters within many states’ priorities contribute to the slow approval process. This analysis provides insights into the Antarctic Treaty System's governance mechanisms, particularly the liability regime and its implementation. The domestic legislation related to Antarctic liability is also analysed. This paper aims to explain the cumbersome approval process of Annex VI and to serve as a cautionary tale for future liability developments.